0.5*(c+2.8)-c=0.6c+0.3

Simple and best practice solution for 0.5*(c+2.8)-c=0.6c+0.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5*(c+2.8)-c=0.6c+0.3 equation:


Simplifying
0.5(c + 2.8) + -1c = 0.6c + 0.3

Reorder the terms:
0.5(2.8 + c) + -1c = 0.6c + 0.3
(2.8 * 0.5 + c * 0.5) + -1c = 0.6c + 0.3
(1.4 + 0.5c) + -1c = 0.6c + 0.3

Combine like terms: 0.5c + -1c = -0.5c
1.4 + -0.5c = 0.6c + 0.3

Reorder the terms:
1.4 + -0.5c = 0.3 + 0.6c

Solving
1.4 + -0.5c = 0.3 + 0.6c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-0.6c' to each side of the equation.
1.4 + -0.5c + -0.6c = 0.3 + 0.6c + -0.6c

Combine like terms: -0.5c + -0.6c = -1.1c
1.4 + -1.1c = 0.3 + 0.6c + -0.6c

Combine like terms: 0.6c + -0.6c = 0.0
1.4 + -1.1c = 0.3 + 0.0
1.4 + -1.1c = 0.3

Add '-1.4' to each side of the equation.
1.4 + -1.4 + -1.1c = 0.3 + -1.4

Combine like terms: 1.4 + -1.4 = 0.0
0.0 + -1.1c = 0.3 + -1.4
-1.1c = 0.3 + -1.4

Combine like terms: 0.3 + -1.4 = -1.1
-1.1c = -1.1

Divide each side by '-1.1'.
c = 1

Simplifying
c = 1

See similar equations:

| 4[4-(5x-7)]=140x+212 | | -3x=3+2(x+1) | | x+2=7x-3 | | 3x-4/4=2 | | 7x^2y+4xy^2-7yx^2+6-7y^2x= | | (2x+4)+(x+32)+(46)=180 | | 10m+3= | | x^2-x-2=154 | | sinx=-0.4 | | 2+3(4x-6)=6-5(2x+1) | | x^2-1x-2=144 | | 5/3y=30 | | x^2-2x-2=144 | | 2(2y-9)-2y=2(y-2)-5 | | X+3=3x+14 | | 6n-2n+9=-3n+144-8n | | 2x*x=-6 | | 6n-n+9=-3n+144-8n | | 4w-6=16-7w | | 2(3z+4)-5=4z+7 | | n^2-2n-1=154 | | x^3+x^2-78=0 | | g(x)=6x-7 | | 2(4+n)-5forn=0 | | 5y+13=7y-2 | | -2r-3=6r+4 | | n^2-2n-1=38.5 | | (x/11)=(x/12)-14 | | n^2-2n-2=38.5 | | 6g-4(-6+3g)=1-g | | -5p+6+6p=11 | | -3/5-3/10 |

Equations solver categories